2019
DOI: 10.1021/acs.est.9b00399
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Responses to Exposure to Outdoor Air from the Chinese Spring Festival at the Air–Liquid Interface

Abstract: The Spring Festival is the most important holiday in China. During this time, the levels of particulate matter (PM) as well as gaseous copollutants significantly increase because of the widespread enjoyment of fireworks. The expression patterns of microRNAs may serve as valuable signatures of exposure to environmental constituents. We exposed macrophages to the whole stream of outdoor air at the air–liquid interface aiming at closely approximating the physiological conditions and the inhalation situation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Winter in Beijing is characterized by considerable use of coal-fired heating and high incidence of haze pollution. ,, Daily analysis of PM 2.5 in Beijing from January to February in 2014 showed that on January 16, the first day of Spring Festival transportation, the PM 2.5 concentration rapidly increased to more than 400 μg m –3 and then dissipated rapidly under the action of wind, followed by a minimum on the January 21 (Figure b). However, with an incoming warm front, the PM 2.5 concentration peaked again from January 23 to 25, and then fluctuated continuously, and reached a small peak again on the Lantern Festival (January 30, 2014) of the same year. , After the end of the Spring Festival travel season, the PM 2.5 remained at a low level from January 31 to February 15, which correlated with the break in the peak travel season. After the Spring Festival holiday, due to the travelers returning to Beijing and the associated increase in vehicle emissions, the concentration of PM 2.5 continued to increase and maintained a high level until March 1. , …”
Section: Results and Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Winter in Beijing is characterized by considerable use of coal-fired heating and high incidence of haze pollution. ,, Daily analysis of PM 2.5 in Beijing from January to February in 2014 showed that on January 16, the first day of Spring Festival transportation, the PM 2.5 concentration rapidly increased to more than 400 μg m –3 and then dissipated rapidly under the action of wind, followed by a minimum on the January 21 (Figure b). However, with an incoming warm front, the PM 2.5 concentration peaked again from January 23 to 25, and then fluctuated continuously, and reached a small peak again on the Lantern Festival (January 30, 2014) of the same year. , After the end of the Spring Festival travel season, the PM 2.5 remained at a low level from January 31 to February 15, which correlated with the break in the peak travel season. After the Spring Festival holiday, due to the travelers returning to Beijing and the associated increase in vehicle emissions, the concentration of PM 2.5 continued to increase and maintained a high level until March 1. , …”
Section: Results and Discussionmentioning
confidence: 91%
“…The maximum PM 2.5 concentration in January–February 2014 was 466 μg m –3 (January 16, 2014), while that in January–February 2021 was 254 μg m –3 (February 13, 2021). The weather in Beijing before the Spring Festival in 2021 was not conducive to convective transport, and this combined with the concentrated discharge of fireworks that started before the New Yearʼs Eve resulted in the peak pollution near New yearʼs Eve of that year. ,,, After that, with an incoming cold front, the air quality gradually improved . In addition to a series of policies and regulations to control the haze weather in recent years, the reason why the concentration level did not remain as high as in 2014 after the spring break in 2021 was also closely related to the decrease in the number of people returning to Beijing and the reduction of human activities during the pandemic. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjacent spermatogenic cells and cytokines (IL‐1α, IL‐6, and activin A) can stimulate Sertoli cells to produce anti‐inflammatory factors, which can regulate the response to FSH (Mruk & Cheng, 2015). In the respiratory tract intake pathway, NMs adhere to the alveolar surface and stimulate pulmonary inflammation, which may induce an increase in serum inflammatory cytokines and Sertoli cell activation (Braakhuis et al, 2014; Chen et al, 2014; Ding et al, 2019). Oral administration of NMs can also increase pro‐inflammatory cytokine levels (Park et al, 2010).…”
Section: Potential Mechanisms Of Male Reproductive Toxicitymentioning
confidence: 99%
“…S12 and S13, CA emissions from residential sources in winter were much higher than those in summer due to the heating demand during the former season (Wang et al, 2012;Huang et al, 2015;Li et al, 2017), while emissions from the FMSs showed a similar seasonal trend due to fireworks. During the Chinese Spring Festival, fireworks result in massive pollutant emissions and severe air pollution (Kong et al, 2015;Yao et al, 2019;Ding et al, 2019;Lai and Brimblecombe, 2020). We have investigated the CA emissions from the FMSs in each month and during several related Chinese festivals (CNE, CSF, LF, QF, and ZF).…”
Section: Intense Short-term and Regionally Concentrated Emissionsmentioning
confidence: 99%